EFFECT OF PARENTERAL INFLUENZA VACCINATION ON THE CELL COMPOSITION AND ITS MICROBIOTA OF THE OROPHARYNGEAL SECRETION IN PATIENTS WITH CHRONIC INFLAMMATORY DISEASES OF THE UPPER RESPIRATORY TRACT - M.D. Timchenko; S.V. Timchenko; L.I. Volosevich (Медична наука України, 2021)
Relevance. Until recently, the issues of changes in immunological and microbiological parameters of the oropharynx in vaccinated against viral infections remain insufficiently covered.